A new evaluation procedure for the strut-and-tie models of the disturbed regions of reinforced concrete structures. (1st October 2017) - Zhong, J.T.; Wang, L.; Deng, P.; Zhou, Man
Highlights: A robust evaluation procedure for the strut-and-tie models is proposed. The evaluation procedure can identify the best among many STMs. The procedure can predict the load carrying capacity of specimens. It can also rationally simplify the idealized STMs. The evaluation procedure brings about producing high-performance structures. Abstract: For the same disturbed region (D-region) of concrete structures, different strut-and-tie models (STMs) may be verified by different researchers, and the reinforcement layouts thus vary significantly. To assess conveniently the performance of these D-regions designed using different STMs, an evaluation system is proposed in this paper. The numerical procedure of the evaluation system is developed based on the ANSYS parametric design language (APDL) and the computer-aided strut-and-tie (CAST) design tool. The evaluation process of this system is mainly divided into three parts: preliminary evaluation, further evaluation, and final evaluation. At the beginning, in the preliminary evaluation, proper STMs in which the distribution of ties agrees well with the tensile stress regions are initially selected according to a finite element analysis. Furthermore, a crack propagation simulation is qualitatively executed to further evaluate and determine the locations of the most significant ties, where primary cracks may arise. For a rational STM, there should exist corresponding ties at these crack locations. Finally, by a load carrying capacity simulation, the most efficient design can be quantitatively confirmed. A classical dapped beam with openings is adopted to demonstrate the efficiency and reliability of the evaluation system. The analysis results indicate that the evaluation system exhibits more robust characteristics than traditional experimental methods. Moreover, the use of this system in the design of concrete structures will bring about significant economic benefits (e.g., reductions in time and costs) and produce high-performance structures.